A COMPARATIVE STUDY OF SELECTED PRIVATE BANKS AND NATIONALIZED BANKS WITH SPECIAL REFERENCE TO FINANCIAL PERFORMANCE - Pokale, Amitkumar Prakashrao; Shetiya, . Mahavir Manikchand (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper provides a comparative analysis of the financial performance of selected private banks and nationalized banks in India. By examining various financial parameters such as profitability, asset quality, and capital adequacy, the study aims to highlight the key differences and similarities between these two categories of banks. The findings will provide insights into the operational efficiencies and financial health of private versus nationalized banks, contributing to a better understanding of the banking sector in India.